Is development studies becoming too brainy? A comparison of World Development Reports. Issue 2 (17th February 2019) - Sato, Mine
ABSTRACT: This article argues that two types of "brainisation" hinder development studies researchers in their phronetic understanding of poor people's realities. It first provides a literature review on two types of knowledge and their differences, as well as two types of brainisation and how they prevent development studies scholars gaining a holistic understanding of the marginalised. Subsequently, a comparative analysis is conducted on two World Development Reports. Finally, alternative scenarios are outlined for the "debrainisation" of development studies and researchers' mind-sets by learning from the fundamental features of human life.